Analyzing the relationship between government expenditure on economic growth: a case study of Malaysia / Mohamad Aliff Mohd Zani - Mohd Zani, Mohamad Aliff (2022)
Government expenditures include all public sector purchases and services in areas such as education, health, social security, and defence (CFI, 2018). Government expenditures enable governments to produce or purchase commodities and services needed to achieve social and economic objectives. Globally, governments have changed dramatically in function and size over time. In the twentieth century, governments worldwide began spending more money on education, healthcare, and social security. Cunently, wealthier governments spend more of their GDP than poor ones. Other than that, most of the governments rely on the private sector to develop and manage products and services, as well as fund, plan, build, and manage public-private partnerships. Government expenditure is intended to provide products and services that the private sector cannot deliver, such as defence, roads, and bridges, as well as welfare payments and benefits. Moreover, government funding can help financially disadvantaged sectors operate or thrive. Finally, greater government spending on education and training is essential to boost worker productivity. This paper will analyse the relationship of government expenditure to the economy growth rate and also some other variable is included to complete the equation which is inflation rate, interest rate, export and unemployment. The data collection that will be uses to run this study is from 2005 to 2021. Therefore, the present study is wants to find out at government expenditure, inflation rate, interest rate, export and unemployment rate will give significant relationship to the Malaysia economic growth and we would also like to know that whether larger government expenditure can give a huge relationship to the economic growth for Malaysia.